Amplitude-robust metastructure with combined bistable and monostable mechanisms for simultaneously enhanced vibration suppression and energy harvesting - Xu, Che (2023)
This Letter reports an amplitude-robust nonlinear dual-functional metastructure that combines bistable and monostable-hardening mechanisms in the local resonators for simultaneous energy harvesting and vibration suppression. The concept is verified by experiments using a primary beam with six pairs of piezoelectric cantilevered oscillators and numerical analyses using a fully coupled electromechanical model for varying base vibration acceleration and load resistance. The results show that the design offers a wide bandgap at high accelerations, attenuation of transmission peaks, and generation of power over a broad bandwidth, outperforming its linear, pure bistable, and pure monostable counterparts. The dual-functional capabilities are further quantitatively assessed by using a weighted index that reflects both the vibration and power generation behaviors. This study demonstrates opportunities in development of the smart nonlinear metastructures for simultaneous vibration suppression and energy harvesting.